An Overview of Chili Leaf Curl Disease: Molecular Mechanisms, Impact, Challenges, and Disease Management Strategies in Indian Subcontinent - Shingote, Prashant Raghunath; Wasule, Dhiraj Lalji; Parma, Vaishnavi Sanjay; Holkar, Somnath Kadappa; Karkute, Suhas Gorakh; Parlawar, Narsing Devanna; Senanayake, D. M. J. B. (Frontiers in Microbiology, 2022)
Leaf curl disease in chili is caused mainly by Chili leaf curl virus (ChiLCV) (Family: Geminiviridae, Genus: Begomovirus). ChiLCV having widespread occurrence in most of the chili (Capsicum spp.) growing regions. ChiLCV has a limited host range and infecting tomato (Solanum lycopersicum), potato (Solanum tuberosum) and amaranth (Amaranthus tricolor). The virus genome is monopartite circular single-stranded DNA molecule of 2.7 kb and associated with α and β-satellites of 1.3 kb and 1.4 kb, respectively. The virus genome is encapsulated in a distinct twinned icosahedral particles of around 18 - 30 nm in size and transmitted by Bemisia tabaci (Family: Aleyrodidae, Order: Hemiptera). Recently, bipartite begomovirus is found to be associated with leaf curl disease. The leaf curl disease has widespread distribution in the major equatorial regions viz., Australia, Asia, Africa, Europe and America. Besides the PCR, qPCR, LAMP based detection systems, recently, Localized Surface-Plasmon-Resonance (LPSR) based optical platform is used for ChiLCV detection in a 20–40 μL of sample volume using aluminum nanoparticles. Management of ChiLCV is more challenging due to vector-borne nature of the virus, therefore integrated disease management strategies need to be followed to contain the spread and heavy crop loss. CRISPR/Cas mediated virus resistance has gained importance in disease management of DNA and RNA viruses due to certain advantages over the conventional approaches. Therefore, CRISPR/Cas system mediated resistance need to be explored in chili against ChiLCV.